2015
DOI: 10.19173/irrodl.v16i3.1984
|View full text |Cite
|
Sign up to set email alerts
|

The use of a mobile learning management system at an online university and its effect on learning satisfaction and achievement

Abstract: This study investigates online students' acceptance of mobile learning and its influence on learning achievement using an information system success and extended technology acceptance model (TAM). Structural equation modeling was used to test the structure of individual, social, and systemic factors influencing mobile learning's acceptance, and how said acceptance influences learning satisfaction and achievement. Unlike earlier TAM-related research that did not provide a broad view of technological acceptance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 46 publications
6
71
0
1
Order By: Relevance
“…Researchers have found TAM to be widely applicable and, in general, a parsimonious theoretical construct (Venkatesh & Davis, 2000;King & He, 2006). Empirically supported across many studies, TAM has also been positively used within the e-learning context (Juan, Chiu, & Francisco, 2006;Shin & Kang, 2015;Giesbers et al, 2013). Selim (2003), and Sun, Tsai, Finger, Chen, and Yeh (2008) found that perceived usefulness and perceived ease of use are important indicators of online course acceptance.…”
Section: Moocs (Massive Open Online Courses)mentioning
confidence: 98%
See 1 more Smart Citation
“…Researchers have found TAM to be widely applicable and, in general, a parsimonious theoretical construct (Venkatesh & Davis, 2000;King & He, 2006). Empirically supported across many studies, TAM has also been positively used within the e-learning context (Juan, Chiu, & Francisco, 2006;Shin & Kang, 2015;Giesbers et al, 2013). Selim (2003), and Sun, Tsai, Finger, Chen, and Yeh (2008) found that perceived usefulness and perceived ease of use are important indicators of online course acceptance.…”
Section: Moocs (Massive Open Online Courses)mentioning
confidence: 98%
“…Therefore, given the robust nature of the TAM theory (Venkatesh & Davis, 2000;King & He, 2006) and considerable empirical support within the in e-learning domain (Juan et al, 2006;Shin & Kang, 2015;Giesbers et al, 2013), researchers should seriously consider learner intention to accept a MOOC when designing such courses. In the current study, the MOOC practiced-oriented course required practical exercises that resulted in utility for learners.…”
Section: Academic Implicationsmentioning
confidence: 99%
“…Recently, TAM has attracted significant attention in e-learning research (Ahuja & Thatcher, 2005;Liaw, 2008;Shin & Kang, 2015;Sun et al, 2008;Teng, 2015;Teo, 2008). Venkatesh & Davis (1996), on the other hand, illustrated that the model can be extended in order to enhance its effectiveness.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…This area of research has not been widely explored in the Middle East in comparison to West countries. We adopted TAM as a foundation because it has been extensively used to investigate technology adoption (Bagozzi, 2007;Shin & Kang, 2015;Sun, Tsai, Finger, Chen, & Yeh, 2008;Wixom & Todd, 2005). Furthermore, the core factors of the model can predict learner satisfaction as well (Liaw, 2008;Sun et al, 2008;Weng & Tsai, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Students at online universities have started to accept mobile technology as a rather new learning tool while the acceptance of mobile devices has influenced their learning achievement both directly and indirectly (Shin & Kang, 2015). However, according to Barreh and Abas (2015), m-learning in the higher education environment has not become widespread as it is still in the testing stage.…”
Section: Mobile Learning (M-learning)mentioning
confidence: 99%